Peruvian testimony of Quechua-speaking female victims: peoples, languages and motherhood - Johansson, Maria Teresa (2023)
This article analyzes the Peruvian testimonies of Angelica Mendoza and Graciela Gamboa presented as statements in face Commission of Truth and Reconciliation and then filmed to be exhibited in the Lugar de la Memoria, la Tolerancia y la Inclusión Social (LUM), in Lima, Perú. These testimonies are interpreted from two theoretical aspects: the first is linked to studies on testimonialism and indigenous subject in Latin America and the second refers to the category of witness and survivor from Auschwitz. Based on this double approach, it is postulated that in these testimonies a political, ethnic and gender victim converges. This feminine subject denounces the extreme conditions of violence and at the same time resists through the linguistic affirmation of the Quechua languague and the Andean Spanish. On the other hand, it is argued that these testimonies problematize gender dimensions linked to motherhood through the extreme figurations of the monstrosity and the corpse that disrupt the thresholds of the human.